Retrospective study of definitive therapy for head and neck mucosal melanoma: The RESUME study - Motoo Nomura; Naomi Kiyota; Yasushi Shimizu; Atsushi Motegi; Tetsuo Akimoto; Takashi Mukaigawa; Takashi Fujii; Nayuta Tsushima; Kiyoto Shiga; Taiji Koyama; Daisuke Kawakita; Akira Ohkoshi; et al. (EJC Skin Cancer, 2025)
Background: Head and neck mucosal melanoma (HNMM) is a rare melanoma. Surgery and radiotherapy (RT) are commonly used; however, their effectiveness remains unclear. In addition, the role of immune checkpoint inhibitors (ICIs) in improving survival in patients with locally advanced HNMM has not been fully evaluated. Patients and methods: This multi-institutional retrospective cohort study analyzed patients with locally advanced HNMM who were treated within the period October 2014 to March 2022. Patients either underwent surgery (S cohort) or received RT (RT cohort). Progression-free survival (PFS) and overall survival (OS) were compared between the S and RT cohorts and between those with and without ICI using propensity score-adjusted models. Results: A total of 304 patients were enrolled: 152 in the S cohort and 152 in the RT cohort. After matching, no significant differences in PFS and OS were observed between the S and RT cohorts. The addition of ICI was associated with significantly improved PFS (hazard ratio 0.50, 95 % confidence interval 0.32–0.80), with a favorable but nonsignificant trend in OS. Subgroup analysis showed that ICI was associated with prolonged OS in the S cohort but had no statistically significant effect in the RT cohort. Disease progression was predominantly distant, irrespective of treatment modality. Conclusion: Surgery and RT were associated with comparable survival outcomes for locally advanced HNMM. ICI was associated with improved PFS, but its relationship with OS needs further investigation. Prospective and randomized studies are needed to refine treatment approaches for this rare malignancy.